(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The library webpages offers platform to the users to navigate the related information about library. This study presents a webometric study focused on the 29 Autonomous Social work college library webpages in India. Study examines the domain extension, internal and external links and total links and total backlinks of Social Work college library webpages. To collect data for this study, smallseotools.com and similarweb.com had used to find out domain authority and page authority of the Social Work Autonomous college library websites covered in this study.